Kanonisasi Tujuh Bacaan Al-Quran: Ibn Mujahid, Otoritas Keilmuan, dan Rekonfigurasi Epistemologis Qiraat - Abdul Jabar; Irfan Fauzi; Umiatu Rohmah; Azhar Ahmad Falahan; Abd. Rahim (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
This study examines the epistemological shift in the canonization of Quranic qiraat during the period of Ibn Mujahid by analyzing the relationship between sanad, riwayah, rasm Uthmani, the acceptance of the qurra community, and Abbasid institutional-political support. Unlike previous studies that emphasize either philological or political aspects, this article focuses on the epistemological consequences of the formation of the seven qiraat. Using a qualitative library-based approach and a historical-critical method, this study analyzes primary sources, especially Ibn Mujahid's Al-Sab'ah fi al-Qira'at and Ibn al-Jazari's Al-Nashr fi al-Qira'at al-'Ashr. The findings show that the seven qiraat represent the institutionalization of Quranic recitational authority through methodological, pedagogical, social, and political considerations. This canonization produced a hierarchy of validity distinguishing accepted canonical readings from anomalous or non-canonical readings, including qiraat shadhdhah.